Land Reform and Conflict in South Sudan: Evidence from Yei River County. Issue 2 (August 2017) - Justin, Peter Hakim; van Dijk, Han
Following South Sudanese independence in 2011, land reform became a major aspect of state building, partly to address historical injustices and partly to avoid future conflicts around land. In the process, land became a trigger for conflicts, sometimes between communities with no histories of "ethnic conflict." Drawing on cases in two rural areas in Yei River County in South Sudan, this paper shows that contradictions in the existing legal frameworks on land are mainly to blame for those conflicts. These contradictions are influenced, in turn, by the largely top-down approach to state building, which has tended to neglect changes in society and regarding land resulting from colonialism and civil wars.